Quality of service and radio management in biomedical wireless sensor networks - Abreu, Carlos
Biomedical wireless sensor networks enable the development of real time patient monitoring systems, either to monitor chronically ill persons in their homes or to monitor patients in step-down hospital units. However, due to the critical nature of medical data, these networks have to meet demanding quality of service requirements, ensuring high levels of confidence to their users. These goals depend on several factors, such as the characteristics of the network deployment area or the network topology. In such context, this chapter surveys the main applications of biomedical wireless sensor networks, taking into account the key quality of service requirements of each one of them. Finally, it presents an analytic method, and its experimental validation, to help engineers managing the radio power of the network nodes in order to improve the communications and the quality of service provided by the network while minimising the energy consumption and, thus, maximising the network lifetime.